Sagot :
This is an arithmetic sequence since there is a common difference between each term. In this case, adding
4
4
to the previous term in the sequence gives the next term. In other words,
a
n
=
a
1
+
d
(
n
−
1
)
a
n
=
a
1
+
d
(
n
-
1
)
.
Arithmetic Sequence:
d
=
4
d
=
4
This is the formula of an arithmetic sequence.
a
n
=
a
1
+
d
(
n
−
1
)
a
n
=
a
1
+
d
(
n
-
1
)
Substitute in the values of
a
1
=
12
a
1
=
12
and
d
=
4
d
=
4
.
a
n
=
12
+
(
4
)
(
n
−
1
)
a
n
=
12
+
(
4
)
(
n
-
1
)
Simplify each term.
Tap for fewer steps...
Apply the distributive property.
a
n
=
12
+
4
n
+
4
⋅
−
1
a
n
=
12
+
4
n
+
4
⋅
-
1
Multiply
4
4
by
−
1
-
1
.
a
n
=
12
+
4
n
−
4
a
n
=
12
+
4
n
-
4
Subtract
4
4
from
12
12
.
a
n
=
4
n
+
8
4
4
to the previous term in the sequence gives the next term. In other words,
a
n
=
a
1
+
d
(
n
−
1
)
a
n
=
a
1
+
d
(
n
-
1
)
.
Arithmetic Sequence:
d
=
4
d
=
4
This is the formula of an arithmetic sequence.
a
n
=
a
1
+
d
(
n
−
1
)
a
n
=
a
1
+
d
(
n
-
1
)
Substitute in the values of
a
1
=
12
a
1
=
12
and
d
=
4
d
=
4
.
a
n
=
12
+
(
4
)
(
n
−
1
)
a
n
=
12
+
(
4
)
(
n
-
1
)
Simplify each term.
Tap for fewer steps...
Apply the distributive property.
a
n
=
12
+
4
n
+
4
⋅
−
1
a
n
=
12
+
4
n
+
4
⋅
-
1
Multiply
4
4
by
−
1
-
1
.
a
n
=
12
+
4
n
−
4
a
n
=
12
+
4
n
-
4
Subtract
4
4
from
12
12
.
a
n
=
4
n
+
8